Socio-demographic patterns of public, private and active travel in Latin America: Cross-sectional findings from the ELANS study - Ferrari, Gerson Luis de Moraes (2020)
Background Active travel such as walking or cycling has been associated with more favorable health outcomes. However, evidence on patterns of transportation in Latin America is scarce. Therefore, the aim of this study was to quantify and characterise socio-demographic patterns of public, private and active travel in Latin American countries. Methods Data from the Latin American Study of Nutrition and Health, a population-based, cross-sectional survey conducted in eight Latin American countries including Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru and Venezuela (n = 9218; age range: 15–65 years). Transportation modes include public (bus, taxi, subway and train), private (car and motorcycle) and active (walking and/or cycling). Outcomes for this study include time spent in different modes of transportation. We performed overall and country-specific descriptive analyses to examine differences by sex, age, socioeconomic and education level. Results For the overall cohort, public transport represent 34.9% of the total travel time, whereas private, walking and cycling represent 48.2%, 10.6% and 6.3% of the total travel time. Time spent using public travel was highest in Venezuela (48.4%); Peru had the highest proportions of private travel (52.5%); Time spent walking and cycling was highest in Costa Rica (14.8% and 12.2%, respectively). The average travel time spent in public and private transport were 299.5 min/week (95% CI: 292.4307.0) and 379.6 min/week (95% CI: 368.0, 391.5) respectively; figures for walking and cycling were 186.9 min/week (95% CI: 181.8, 191.9) and 201.1 min/week (95% CI: 187.8, 216.9). Conclusions Public and private transport were the most common forms of travel in Latin America. Active travel (walking or cycling) represent 17% of total physical activity, therefore, promoting and providing the right infrastructure for active commuting could translate in increasing the population overall levels of physical activity in Latin America.